Evaluation of Adverse Drug Reactions (ADRs) in Breast Cancer Patients Who Received Doxorubicin, Cyclophosphamide (AC) and Doxorubicin, Cyclophosphamide, Paclitaxel (AC-T) Chemotherapy at West Nusa Tenggara Provincial Hospital - Baiq Lenysia Puspita Anjani; Baiq Nurbaety; Baiq Leny Nopitasari; Rahma Nanda Muriani (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Chemotherapy is commonly used to treat breast cancer (BC). Chemotherapy may cause ADRs in patients, affecting their physical and psychological wellbeing. Objective: To understand the adverse drug reaction (ADR) profile in patients with breast cancer who received AC-T and AC chemotherapy at the West Nusa Tenggara Provincial Hospital. Methods: This observational study used cross-sectional data collected from medical records and direct interviews with the patients between May and June. Probability categories were measured using the Naranjo algorithm questionnaire, causality categories were measured using a causality flowchart, and the severity level of ADRs was determined using the Common Terminology Criteria for Adverse Events (CTCAE) 5.0. Results: The probability results for the AC-T regimen were as follows: possible (10 %), probable (54.44 %), and definite (35.56 %). whereas The AC regimen showed categories of possible (6.67%), probable (63.33%), and definite (30%). The causality results for the AC-T regimen were categorized as unlikely (1.11%), possible (12.22%), probable (25.56%), or certain (61.11%), whereas those for the AC regimen were categorized as possible (6.67%), probable (43.33%), or certain (50%). The most common ADRs were alopecia and nausea, with the highest probability in the probable category for AC-T (54.44%) and AC (63.33%), respectively. Conclusion: Respondents who received the AC-T regimen experienced more severe ADRs in terms of hematologic disorders (anemia, leukopenia, and thrombocytopenia) and symptoms of nausea, pain, and fever than those who received the AC regimen.